The Economics of Intellectual Property Rights in China Patents, Trade, and Foreign Direct Investment - Liegsalz, Johannes; SpringerLink (Online service) (Wiesbaden : Gabler, 2010)
The protection of intellectual property rights (IPRs) is a contentious issue in developing and emerging economies. While countries like China are often reluctant to strengthen IPRs, industrialized countries complain about welfare losses in their markets due to foreign counterfeiting and piracy. In this context, Johannes Liegsalz empirically analyzes the legal framework and the economic relevance of patents in the People$1 (Bs Republic of China. His results show that IPRs play a vital role in contemporary China and that they have a positive impact on international trade flows and foreign direct investments.s
Patent Examination at the State Intellectual Property Office in China -- The Relationship between Trade and Intellectual Property Rights in China -- The Relationship between Foreign Direct Investments and Intellectual Property Rights in China -- Conclusion.
Keywords: Economics; Technology; Economics/Management Science; Technology Management